Diagnostic challenges in the assessment of psychiatric illness among persons with speech and hearing impairments in India - Sincy Treesa Joseph; Aishwarya Rao; Shalini Perugu; Bhuvaneshwari Sethuraman (Annals of Indian Psychiatry, 2023)
The prevalence of psychiatric illness among the hearing impaired does not vary from the general population. This case series highlights two different presentations of psychiatric illness in speech and hearing-impaired patients. The first case describes a patient that was diagnosed to have unspecified nonorganic psychosis after a detailed assessment and observation. The second case describes the challenges in diagnosing depression versus organicity. Difficulties in communication act as a barrier to psychiatric assessment, and there are no clear guidelines for the same. Both of these cases summarize the challenges faced in assessment, mental status examination, the lack of knowledge of linguistics hindering assessment, and the paucity of literature on psychiatric problems in speech and hearing impaired, especially in India. We found that these may be overcome by consistent ward observation, assessment of psychomotor activity, affect, functional analysis of aggression, and course and duration of the presenting illness.